BeesAnts: a new nature-inspired routing algorithm. (1st January 2013) - Al Maghayreh, Eslam; Al-Haija, Sallam Abu; Alkhateeb, Faisal; Aljawarneh, Shadi; Al-Shawakfa, Emad
In this paper, we have introduced a new multi-agent nature-inspired routing algorithm. The algorithm is referred to as the BeesAnts algorithm. It is a combination of the ant colony-based routing algorithm (ARA) and the BeeHive-based routing algorithm. The proposed routing algorithm works effectively on networks consisting of two parts; one is a fixed network and the other is a mobile ad hoc network (MANET). It applies the ARA routing algorithm on the mobile part and the BeeHive routing algorithm on the fixed part. The experimental results and the statistical analysis have demonstrated that the BeesAnts routing algorithm outperforms its ancestor, the ARA routing algorithm, in terms of the propagation delay, the queue delay, and the number of hops.